A managerial perspective of determinants of entry into Malaysia's electrical and electronic product manufacturing industry. - Thanasegaran, Ganesh G. (McGraw Hill, 2012)
A discussion of the factors influencing/determining entry into the electrical and electronic product manufacturing industry in Malaysia from a managerial perspective.